Isolated Spontaneous Midbrain Hemorrhage in a 14-Year-Old Boy - Nguyen, Kim-Long R.; Kim, Hyunyoung; Nagy, Laszlo (Journal of Neurological Surgery Reports, 2017)
Isolated spontaneous midbrain hemorrhages are rare because they are usually secondary to hemorrhages from inferior structures such as the pons and cerebellum, or superior structures such as the thalamus and putamen. While the etiologies are largely unidentified, the most common ones are vascular malformations and bleeding diathesis with hypertension being relatively uncommon. We report midbrain hemorrhage in a 14-year-old boy with a long-standing history of frequent migraine headaches and attention deficit/hyperactivity disorder (ADHD). Neurologic examinations, noncontrast computed tomography (CT) scans, and magnetic resonance imaging (MRI) suggested that the lesion likely affected the dorsal part of the midbrain. The neurologic symptoms improved following endoscopic third ventriculostomy (ETV) with the placement of external ventricular drains (EVDs). In this report, anatomical correlations to the case are discussed and previous reports of midbrain hemorrhages are reviewed.
Keywords: isolated hemorrhage; midbrain hemorrhage; pediatric; spontaneous midbrain hemorrhage